Perlindungan Hukum Bagi Pemegang Sertipikat Hak Atas Tanah yang Perolehannya Secara Itikad Baik - Riany Linggar Sari; Hanafi Tanawijaya (Syntax Literate, 2023)
The transfer of land through dowry is one of the legal means of transfer in the eyes of the law. Proof of the transition contained in the marriage certificate citation can be used as a basis for the right to issue a marriage title certificate. However, there are many land disputes in Indonesia, one of which is issuing certificates without the knowledge of the original owner. This is against the law. This research uses a type of normative legal research, namely legal research conducted by looking for sources or research data through libraries or using secondary data and tertiary legal materials. This study has two objectives, namely knowing the legal protection for land certificate holders whose acquisition is in good faith and knowing the legal consequences that occur if the buyer defaults on the land certificate holder. The result of this study is that the quotation of a marriage certificate containing a land dowry in it can be used as a refutation if the other party makes a land title certificate with his own name. Dowry in Islam is a compulsory gift that cannot be taken back except at the pleasure of the wife. Wives can sue the other party through three ways: discussion, arbitration and court. The legal consequences that occur in the event of default on the dowry award are that the violator has absolute responsibility to prove all his actions are correct and the injured party can claim compensation to the court